1989
DOI: 10.1172/jci114247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor cell growth by interferon-gamma is mediated by two distinct mechanisms dependent upon oxygen tension: induction of tryptophan degradation and depletion of intracellular nicotinamide adenine dinucleotide.

Abstract: Growth of a variety of human tumor cell lines is inhibited by interferon-y (IFN-,y) in vitro. This mechanism is not well understood. The present experiments identify two separate mechanisms which account for the growth inhibitory activity of IFN-'y. Cell lines most sensitive to IFN-'y (inhibited by 10-30 U/ml IFN-y in 3 d) were stimulated by IFN-'y to oxidize tryptophan in media to kynurenine and completely eliminated tryptophan from the culture media after 48-72 h. Addition of L-tryptophan, but not other aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 46 publications
4
55
0
2
Order By: Relevance
“…The ability of IFN-7 to induce programmed cell death is consistent with previous reports that suggested a role for this cytokine in the negative selection by apoptosis of the peripheral T-and B-lymphocyte repertoire {Liu and Janeway 1990; Grawunder et al 1993). IFN-~/has been long known as a cytokine causing the pathological type of cell death (termed necrosis) (Aune and Pogue 1989). So as with TNF-a (Laster et al 1988), IFN-7 can induce either pathological or physiological cell death depending on the target cells.…”
Section: Discussionsupporting
confidence: 88%
“…The ability of IFN-7 to induce programmed cell death is consistent with previous reports that suggested a role for this cytokine in the negative selection by apoptosis of the peripheral T-and B-lymphocyte repertoire {Liu and Janeway 1990; Grawunder et al 1993). IFN-~/has been long known as a cytokine causing the pathological type of cell death (termed necrosis) (Aune and Pogue 1989). So as with TNF-a (Laster et al 1988), IFN-7 can induce either pathological or physiological cell death depending on the target cells.…”
Section: Discussionsupporting
confidence: 88%
“…IDO activation can result from lipopolysaccharide and cytokine stimulation, particularly interferon-γ (IFN-γ) (Byrne et al, 1986). Low tryptophan concentrations induced by IDO are associated with inhibited proliferation of viruses, protozoan parasites and other pathogens and also with decreased proliferation of tumor cells (Gupta et al, 1994;Aune and Pogue, 1989). Recent studies have suggested a role for IDO in the regulation of T cell responses, either by lymphocyte deprivation of tryptophan or by induction of the tryptophan metabolites, 3-OH-kynurenine and 3-OHanthranilic acid which inhibit T-cell reactivity (Terness et al, 2006;Terness et al, 2002;Frumento et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Under some pathologic conditions, induction of the initial and rate-limiting enzyme of the kynurenine pathway, indoleamine 2,3-dioxygenase (IDO), also leads to a significantly increased metabolism of tryptophan by the kynurenine pathway (Saito et al, 1992). Recently, interest in tryptophan metabolism via this pathway has grown due to the recognition that induction of IDO by interferon gamma leads to local tryptophan depletion, thus inhibiting cell growth in malignant tumors (Ozaki et al, 1988;Aune and Pogue, 1989;Taylor and Feng, 1991;Burke et al, 1995). This observation has led to the proposal that pharmacological induction of IDO might be an effective way to slow down tumor cell growth.…”
Section: Introductionmentioning
confidence: 99%